1994
DOI: 10.1007/bf00866371
|View full text |Cite
|
Sign up to set email alerts
|

Renal disorders in children: a Nigerian study

Abstract: A 5-year prospective study of 699 children with various renal disorders from around the Rivers State, which is in the eastern part of Nigeria, was carried out to investigate the prevalence and significance of renal disorders in a third world country with no facilities for paediatric dialysis and transplantation. Renal disorders accounted for 1.1% of the total outpatients and hospital admissions. The commonest renal disorders were urinary tract infection (UTI, 68.9%); nephrotic syndrome (NS 14.6%) and acute pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
54
4

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 9 publications
11
54
4
Order By: Relevance
“…In our study, UTI was the most common renal disorder, which was similar to the findings of studies conducted in Pakistan, [8] Sudan, [12] Benin, [13] Port Harcourt, [14] and Venezuela, [16] but differed from findings in Jos, [2] Calabar, [5] Lagos, [6] Enugu, [9] and Iran. [15] This was followed by AGN and AKI, which showed that infectious agents play a role in renal diseases in Gusau, as seen in other reports.…”
Section: Researchsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, UTI was the most common renal disorder, which was similar to the findings of studies conducted in Pakistan, [8] Sudan, [12] Benin, [13] Port Harcourt, [14] and Venezuela, [16] but differed from findings in Jos, [2] Calabar, [5] Lagos, [6] Enugu, [9] and Iran. [15] This was followed by AGN and AKI, which showed that infectious agents play a role in renal diseases in Gusau, as seen in other reports.…”
Section: Researchsupporting
confidence: 88%
“…The childhood renal diseases identified in our study were similar to what was obtained in studies conducted elsewhere in Nigeria [1,2,5,6,13,14] and the world; [7,[15][16][17] however, with varying rates. This observation could be explained by the fact that environmental factors, such as poor hygiene, poverty, and socioeconomic conditions, as well as genetic factors and late presentation, may have influenced the rates of childhood kidney diseases in our setting.…”
Section: Researchsupporting
confidence: 86%
“…5 In the Nigerian study 6 this rate was only 22% while in Saudi Arabian trial it was as high as 84%. 7 Among our patients 80.4% were initially responsive to steroid treatment and 19.6% were unresponsive.…”
Section: Discussionmentioning
confidence: 94%
“…Long hours of standing can be responsible for abnormally elevated protein excretion, which however returns to normal in recumbent position. Several studies however have shown that there is a high incidence of renal diseases and a correspondingly high morbidity and mortality from chronic renal failure in Nigerian children (Eke and Eke 1994).…”
Section: Introductionmentioning
confidence: 99%